Алгебра оцінок у слабоструктурованій системі переваг ОПР - Бобало, І. Ю.; Катренко, А. В. (Видавництво Національного університету “Львівська політехніка”, 2020)
This paper describes a set of operations and functions at estimations and preferences in semistructured decision problem, with preferences representation in the estimation hypercube form.
Keywords: 681.3